Oscillation damping improvement in the Lao PDR power system by power system stabilizer (Thai) - Sadettan, Somsanith; Hungsasutra, Sumrit; Binsomprasong, Phongsak; Triyangkulsri, Jittipath (Asia-Pacific Journal of Science and Technology, 2017)
This paper presents a damping improvement for the Lao PDR-EGAT R2 Thailand tie-line power oscillation mode. This oscillation mode corresponds to an electromechanical oscillation mode between the Nam Ngum 1 generator in the Lao PDR system and machines in the EGAT system. This mode is partially influenced by the Nam Ngum 1 in the Lao PDR system. A power system stabilizer (PSS) will be installed at the Nam Ngum 1 generator to improve the initial mode damping of the machine. The designed PSS is a lead-lag compensation employing the generator angular speed deviation as the input signal. By applying modal control theory, suitable parameter values for the PSS can be determined. From the simulation using the PSS/ E program, the designed PSS at the Nam Ngum 1 generators can significantly improve the tie-line oscillation as required.